ANALISIS MINAT MENABUNG NASABAH PADA MASA PANDEMI COVID 19 DI BANK KALBAR SYARIAH CABANG SINGKAWANG - Elsa Nathasa; Iwan Kusnadi (Cross-border, 2021)
The results of this study indicate that; First, the interest in Saving Customers During the Covid 19 Pandemic is Interested, where the number of customers has increased from the previous year. The 5 components that influence customer interest in saving during the COVID-19 pandemic are: Attention, Interest, Disregard, Confidence, Feelings of Happiness. A number of customers have barriers to saving because the income they get is only enough for their daily needs and cannot be set aside for savings. Second, the efforts made by the Bank to Increase Customer Interest During the Covid 19 Pandemic is the 4P Marketing Mix, namely Product, Price, Place, Promotion, but socialization in schools cannot be carried out because schools are conducted online not face-to-face as usual so that hard to socialize. Facing these problems, the Bank goes directly to the community to carry out promotions while still complying with health protocols and promoting through the internet site.